Changing the Paradigm of Atherosclerosis - Vinall, Phil (MD Conference Express, 2010)
Atherosclerosis is a diffuse process that starts early in childhood and progresses asymptomatically through adult life, often manifesting as coronary artery disease, stroke, transient ischemic attack, or peripheral arterial disease before the problem can be identified. Rupture of atherosclerotic plaque and its thrombotic complications are the major cause of acute coronary syndrome and cardiovascular death in the industrialized world. This article discusses some of the research that has advanced our understanding of the atherosclerotic process.